Analisis Tingkat Kesehatan Laporan Keuangan pada PT BPRS - Nadhifah Fairuz Salma; Muhammad Iqbal Surya Pratikno (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Bank health is a very important thing, because bank health is a description of the condition of banking performance in carrying out its operational activities. This study uses the rgec method to calculate the soundness of a bank. The influencing factors in using the rgec method include risk profile, good corporate governance, earnings, and capital. The purpose of this study was to determine the soundness of banks at BPRS Bhakti Sumekar in 2015-2020. The research method used in this research is descriptive research with a quantitative approach, namely explaining the object to be studied by providing a description of the problem that has been identified and carried out intensively and in detail in a company. The results of the research at BPRS bhakti semekar in 2015-2020, namely the FDN value was in a healthy condition. ROA and BOPO values ​​are in a very healthy condition and consistently increase. Meanwhile, the ROE value has decreased some but is still categorized in a fairly healthy condition. The CAR value is in a very healthy condition. Keywords: Author RGEC; Syariah Bank; Healty Bank